Experience of nurses in identifying delirium among cancer patients: A qualitative study - Huda, Nurul; Deli, Hellena; Wahyuni, Sri; Erwin; Pranata, Satriya; Wahyuni, Sri (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Information about how nurses screen for delirium in cancer patients can provide insights into improving recognition. This study aimed to investigate the experiences of nurses while identifying delirium in cancer patients. Methods: The study's design was qualitative, using thematic analysis. Data were gathered via a focus group discussion with ten nurses from two oncological wards of Nursing and Health Research Universitas Riau, Pekan Baru Riau, Indonesia. The focus group discussion lasted roughly 90 minutes. Participants provided feedback on their experiences with assessment in delirium through semi-structured and open-ended questions. Data collection occurred in September 2023 at two oncology wards. Data analysis in this phenomenological research used the Collaizzi method to describe the meaning of an experience identified through the important themes of a phenomenon consisting of seven stages. Results: Categories, subcategories and themes were constructed. Experiences of nurses in identifying delirium among cancer patients were identified i) delirium, agitation and confusion are almost similar (the term delirium is not well known, and the type of delirium is not familiar); ii) tools for assessing delirium are needed (the tool does not exist and is unknown, used clinical experiences supported by laboratory testing); and iii) nurses can play an important role in identifying delirium (important role in assessing delirium, advising to prevent delirium among healthcare professionals). Conclusion: Nurses who work in oncology wards need to know more about delirium screening since they play an important role in early detection and treatment. Therefore, appropriate knowledge and measurement tools are required to identify delirium earlier among cancer patients.